Vunus Observed : A comedy - Fry, Christopher (London : Geoffrey cumblerlege, 1951)
The Catholic University, Speech and Drama Department, Rev. G.V. Hartke, O.P., head presents "Thor, With Angels," a play by Christopher Fry, staged by Leo Brady, setting and lighting by James Waring, performances coached by Josephine McGarry Callan, costumes designed by Joseph Lewis, costumes executed by Anne Tacik.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English comedy; Theater programs -- Washington (D.C.); Theater programs -- 1950.